Capital Expenditure Dynamics and Infrastructural Growth Nexus: Evidence from an oil - dependent economy - Igbinedion, Sunday Osahon; Nnadozie, Obianuju Ogochukwu (Ekonomi Bisnis, 2021)
The role of infrastructure in promoting economic development has long been acknowledged in the economic literature. In Nigeria, the basic physical infrastructure deficit has been identified as a major drag in the country's prospects for development. One major source of infrastructure financing is government capital expenditure. Unfortunately, capital expenditure over the years has been characterized by wide fluctuations, with attendant consequences on the level of infrastructural development. Thus, this study seeks to investigate the nexus between capital expenditure dynamics and infrastructural performance within the Nigerian context, utilizing the Fully Modified Ordinary Least Square (FMOLS) and Error correction procedure (ECM) and data from 1981 to 2018. Findings suggest that both capital expenditure dynamics and inflation rate have a negative and statistically significant impact on the level of infrastructure while the impact of foreign aid on infrastructural development was positive and significant. Accordingly, we recommend among others, the need for a suitable macroeconomic and regulatory framework that will encourage active private sector participation to sustainably support infrastructure investment. The monetary authorities can complement such efforts by implementing policies that will guarantee at most single-digit inflation rate in the economy.